Iran’s Multilateral Diplomacy on The International Atomic Energy Agency (IAEA) Related to The Development of Nuclear Energy 2009-2015 - Ibnu Qoyyim, Al Hafizh (Department of International Relations Universitas Pertamina, 2022)
Since the Islamic revolution of Iran in 1979, the United States and its allies don’t like Iran's nuclear program and aim to manufacture nuclear weapons and assumed that Iran’s nuclear has violated the NPT treaty. Over time Iran sanctions in the form of a resolution by the UN Security Council due to the allegations provided by the United States and its allies. To maintain and acquire nuclear development rights, the Iranian government conducts diplomacy with the IAEA as an international atomic agency. This research explains influential factors in multilateral diplomacy success by Iran on IAEA related to nuclear energy development during 2009-2015 using the concept of multilateral diplomacy by Ronald A. Walker. The method used is qualitative method with descriptive analysis and data collection techniques are the study of literature. Iran is considered successful multilateral diplomacy through the formation of a collective agreement in the form of a comprehensive Joint Plan of Action (JCPOA) in 2015 in Vienna. The Iranian government has been actively disseminating information related to nuclear development, as well as adhering to the multilateral treaty that has been ratified as the NPT safeguards agreement and additional protocol. the Iranian government actively negotiated since 2009 to send a delegation to the various meetings